2019
DOI: 10.1111/imm.13044
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐35 in immune‐related diseases: protection or destruction

Abstract: Summary Interleukin‐35 (IL‐35) is a recently identified heterodimeric cytokine in the IL‐12 family. It consists of an IL‐12 subunit α chain (P35) and IL‐27 subunit Epstein–Barr virus‐induced gene 3 (EBI3) β chain. Unlike the other IL‐12 family members, it signals through four unconventional receptors: IL‐12Rβ2–IL‐27Rα, IL‐12Rβ2–IL‐12Rβ2, IL‐12Rβ2–GP130, and GP130–GP130. Interleukin‐35 signaling is mainly carried out through the signal transducer and activator of transcription family of proteins. It is secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 91 publications
(189 reference statements)
0
42
0
Order By: Relevance
“…To the best of our knowledge, this was the first study on the direct regulatory role of IL-35 to CD14 + monocytes in Kawasaki disease. We showed an elevation of plasma IL- 35 Recent studies have revealed abnormal expression of IL-35 in inflammatory autoimmune diseases, and suggested the critical regulatory role in the onset and development of these diseases [21,22]. Decreased expression of peripheral IL-35 was reported in patients with systemic lupus erythematosus [23], multiple sclerosis [24], primary Sjogren's syndrome [25], and psoriasis vulgaris [26].…”
Section: Discussionmentioning
confidence: 69%
“…To the best of our knowledge, this was the first study on the direct regulatory role of IL-35 to CD14 + monocytes in Kawasaki disease. We showed an elevation of plasma IL- 35 Recent studies have revealed abnormal expression of IL-35 in inflammatory autoimmune diseases, and suggested the critical regulatory role in the onset and development of these diseases [21,22]. Decreased expression of peripheral IL-35 was reported in patients with systemic lupus erythematosus [23], multiple sclerosis [24], primary Sjogren's syndrome [25], and psoriasis vulgaris [26].…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, we were able to show that PF-BaE5 and PF-BaE7-primed DCs promoted the polarization of CD4 + T cells towards a regulatory phenotype (CD4 + FoxP3 + IL-10 + ) with an increased expression of the gene encoding Ebi3. Ebi3 is a subunit of the heterodimeric cytokine IL-35, a potent immunosuppressive cytokine secreted by Tregs and B regulatory cells with a strong ability to inhibit T cell differentiation and effector functions [ 76 ]. IL-35-induced Treg cells (iTr35) produce more IL-35 [ 77 ] and type 1 Treg cells (Tr1) use IL-35 to suppress the immune response [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…66,72 Although IFNγ has proinflammatory consequences it has also been described as having pro-tolerogenic actions, through the production of molecules such as IDO, iNOs and FGL2. 66,72 Although IFNγ has proinflammatory consequences it has also been described as having pro-tolerogenic actions, through the production of molecules such as IDO, iNOs and FGL2.…”
Section: Treg Cells 62 Fgl2 Expression Was Then Reported In Mouse Cd8ααmentioning
confidence: 99%
“…IL-35 has been previously described as expressed by CD4 + Tregs 71 but it has also been described as expressed and playing a suppressive role for tumor-associated CD8 + Tregs. 66,72 Although IFNγ has proinflammatory consequences it has also been described as having pro-tolerogenic actions, through the production of molecules such as IDO, iNOs and FGL2. 68 IFNγ has been described as produced by several CD8 + Treg types 3,4,65,[73][74][75][76][77] although the function of IFNγ in CD8 + FOXP3 + cells has not been specifically analyzed.…”
Section: Treg Cells 62 Fgl2 Expression Was Then Reported In Mouse Cd8ααmentioning
confidence: 99%